METALLURGICAL ADVANTAGES OF ROTATION TILTING FURNACES - S. L. Rovin; L. E. Rovin; T. M. Zajats (Литьë и металлургия)
It is shown that introduction of rotary tilting furnaces can be a basis for considerable resources saving, lowering of power inputs, reduction of products cost for Byelorussian machine-building enterprises.